Warts (Verrucae): Nurse interventions - Tatomirovic Vesna (Association of Nurses Technicians and Midwives, 2016)
This article includes defining the nipple, analyze the causes and localization, treatment options and treatment, with emphasis on the advantages of electro destructed treated tissue. In the article emphasize was given to the analysis methods of electro destructed tissue specificity and nurses works in the above treatment, both in the preparation, implementation and processing of treated area after the perpetration of treatment. Featured article shows results of treatment of warts by applying the treatment that the experimental group of 15 treated patients. In particular, it was pointed out a significant place of well educated nurses. The article also points to the positive effects of the method applied dermato-surgical methods.